Penyalahgunaan Keadaan dalam Perjanjian Pinjam Meminjam Uang oleh Rentenir - Ahmad Arif Syarif (Lex Renaissance, 2017)
This study examines, first, what are the benchmarks used by court in determining the misuse of circumstance in loan agreements by loan sharks? Second, what are the legal consequences of loan agreements that contain elements of circumstance misuse? This study is library research with a normative juridical approach to observe the phenomenon of loan sharks from a legal perspective. The results indicate that, first, there are three benchmarks used by court in determining the misuse of circumstance loan agreements, including moral benchmark of fairness and propriety, benchmark of good faith, and benchmark of profit. Secondly, the legal consequences of loan agreements by loan sharks can be void if one of the aggrieved parties requests cancellation before the judge due to misuse of circumstance. This reason is then classified into the fourth defect of will apart from the other three defects of will that have been regulated in the Civil Code.Keywords: Loan agreements, misuse of circumstances